A STUDY ON UNIVERSITY STUDENTS PERCEPTION AND PREFERENCE TOWARDS MOBILE WALLETS, WITH REFERENCE TO PALGHAR DISTRICT - Dr.Surekha B Mishra, Nileshwari V Ghumre, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The major element of the globalized world is technology and development. Considering how tech-savvy the younger generation is, electronic devices have become ubiquitous. Young people use smartphones for everything from personal use to work. The mobile wallet market in India has benefited from the rapid usage of smartphones and mobile internet. Younger generations utilize mobile wallets to make the majority of their payments when connecting with others and conducting business online. M-wallets offer a variety of cybernetic services, from utility to e-commerce activities. The goal of this study is to examine young university students' opinions, preferences, and satisfaction with M-wallet (mobile wallet) in the fast-paced technology era in Palghar district. 52 responses from respondents were compiled and examined using a structured questionnaire procedure. The study's findings will strategically assist manufacturers of smart phones, M-wallet service providers, regulatory agencies, and other financial institutions in reaching out to potential customers.